Antibacterial, Antioxidant and Toxicological Properties of Artemisia annua Essential Oil - Wendan CHEN; Yuying BAI; Chenghu GUO; Yuhong CHAI; Fengjun WANG; Conglin HUANG; Hua LIU (Shipin gongye ke-ji, 2024)
The essential oil of Artemisia annua grown in the Beijing area was extracted by hydrodistillation, and then its volatile components were analyzed by gas chromatography-mass spectrometry (GC-MS). The in vitro antioxidant activity of the Artemisia annua essential oil was determined by measuring the scavenging rate of DPPH and hydroxyl radicals, its antibacterial activity by using the agar diffusion method, and its toxicological properties by perfusing mice with different doses of the essential oil. The results showed that the extraction rate of the Artemisia annua essential oil was 1.04‰, with 332 essential oil components being identified by GC-MS analysis. Of these, 22 components accounted for 71.09% of the total volatiles, with relatively high contents of artemisinone (19.34%) and (+)-α-pinene (6.10%). The Artemisia annua essential oil exhibited good scavenging activities of the DPPH and hydroxyl radicals in a dose-dependent relationship. The highest scavenging rates of the DPPH and hydroxyl radicals were 40.03% and 92.97%, respectively, at an essential oil concentration of 10 mg/mL. The Artemisia annua essential oil significantly inhibited the growth of both Staphylococcus aureus and Escherichia coli, with inhibitory zones of 12.67±0.29 mm and 9.27±0.25 mm, respectively. The LD50 value of the Artemisia annua essential oil was 7491 mg/kg, indicating that it was not toxic. This study can provide a theoretical reference for the extraction and use of Artemisia annua and other Artemisia plants.